Pirates of the Caribbean. At world's end [videorecording (Blu-ray + DVD)] - Verbinski, Gore; Depp, Johnny; Bloom, Orlando, 1977-; Knightley, Keira, 1985-; Skarsgård, Stellan; Nighy, Bill, 1949-; Chow, Yun-fat; Rush, Geoffrey, 1951- (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2011)
Just when he's needed most, Captain Jack Sparrow is trapped on a sea of sand in Davy Jones' Locker. In an increasingly shaky alliance, Will Turner, Elizabeth Swann and Captain Barbossa begin a desperate quest to find and rescue him.